Active-specific immunotherapy of human cancers with the heat shock protein Gp96 - revisited - Randazzo, Marco; Terness, Peter; Opelz, Gerhard; Kleist, Christian (International journal of cancer, 2012)
The passive administration of specific antibodies that selectively target tumors is a well-known strategy in cancer treatment. Active immunotherapy using peptide vaccines, in contrast, is expected to induce specific, cytolytic T cells in the patient, which react against tumor antigens and destroy malignant cells. Although several concepts exist, the identification and low immunogenicity of tumor-specific peptides remain a serious problem. Heat shock proteins (HSPs), notably glycoprotein (Gp) 96, are of special interest, because they are able to take molecular peptide-fingerprints of the protein array characteristic for a particular cell. Association of Gp96 with peptides has been shown to be essential for crosspresentation and activation of T cells. Consequently, Gp96-peptide complexes extracted from cancer cells harbor the tumor-specific peptides and are immunogenic, thus offering a tool for active immunization against the tumor. Already, several immunotherapy studies of human cancers have been carried out, showing no severe adverse effects but unfortunately only limited improvement in the clinical outcome. Vitespen, a commercial HSP-peptide complex vaccine based on tumor-derived Gp96, seems to induce an improved overall survival for subsets of early stage melanoma and kidney cancer patients. The limited access to vaccine material derived from the autologous tumor requires the development of alternative protocols. Moreover, counteracting immunosuppressive mechanisms induced by the malignancy might further improve the efficacy of vaccinations. This review critically analyzes the current state of clinical immunotherapy with Gp96, with special attention to Vitespen.